Biological Designer Self-Assembling Peptide Nanofiber Scaffolds Significantly Enhance Osteoblast Proliferation, Differentiation and 3-D Migration - Horii, Akihiro (Public Library of Science, 2007)
A class of self-assembling peptide nanofiber scaffolds has been shown to be an excellent biological material for 3-dimension cell culture and stimulating cell migration into the scaffold, as well as for repairing tissue defects in animals. We report here the development of several peptide nanofiber scaffolds designed specifically for osteoblasts. We designed one of the pure self-assembling peptide scaffolds RADA16-I through direct coupling to short biologically active motifs. The motifs included osteogenic growth peptide ALK (ALKRQGRTLYGF) bone-cell secreted-signal peptide, osteopontin cell adhesion motif DGR (DGRGDSVAYG) and 2-unit RGD binding sequence PGR (PRGDSGYRGDS). We made the new peptide scaffolds by mixing the pure RAD16 and designer-peptide solutions, and we examined the molecular integration of the mixed nanofiber scaffolds using AFM. Compared to pure RAD16 scaffold, we found that these designer peptide scaffolds significantly promoted mouse pre-osteoblast MC3T3-E1 cell proliferation. Moreover, alkaline phosphatase (ALP) activity and osteocalcin secretion, which are early and late markers for osteoblastic differentiation, were also significantly increased. We demonstrated that the designer, self-assembling peptide scaffolds promoted the proliferation and osteogenic differentiation of MC3T3-E1. Under the identical culture medium condition, confocal images unequivocally demonstrated that the designer PRG peptide scaffold stimulated cell migration into the 3-D scaffold. Our results suggest that these designer peptide scaffolds may be very useful for promoting bone tissue regeneration.